DIGITAL TAX ADMINISTRATION REFORM: AN ANALYSIS OF BEHAVIORAL INTENTION TO USE CORETAX USING THE TECHNOLOGY ACCEPTANCE MODEL APPROACH AND THE MODERATING ROLE OF TAX SOCIALIZATION: Reformasi Administrasi Perpajakan Digital: Analisis Behavioral Intention to Use CoreTax dengan Pendekatan Technology Acceptance Model dan Moderasi Sosialisasi Pajak - Mangngalla, Muliani; Mongan, Frischa Faradilla Arwinda; Viktor, Devika; Bantong, Hersen (Jurnal Pajak dan Keuangan Negara (PKN), 2026)
This study aims to analyze the influence of perceived usefulness and perceived ease of use on the behavioral intention to use the digital taxation system, CoreTax, as well as examine the moderating role of tax socialization. A quantitative approach was employed using Structural Equation Modeling Partial Least Squares (SEM-PLS) for data analysis. Data were collected through questionnaires distributed to taxpayers who have used the CoreTax system. The results indicate that both perceived usefulness and perceived ease of use have a positive and significant effect on behavioral intention to use CoreTax. Furthermore, tax socialization was found to moderate the relationship between perceived ease of use and behavioral intention to use, but not the relationship between perceived usefulness and behavioral intention to use. These findings suggest that the effectiveness of tax socialization is crucial in enhancing user comfort and encouraging the intention of taxpayers to continuously use digital tax services.